The Influence Of Firm Size, Leverage, Liquidity, Cash Turnover On Profitability: Empirical Study of a Food And Beverage Sub-Sector Companies In 2018-2022 - Gunawan, Tipanirah; Ramli, Abdul Haeba (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
This research was conducted to determine and analyze the influence of firm size, leverage, liquidity, cash turnover on profitability in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the period 2018-2022 with a population of 26 companies. The sampling technique used in this research was purposive sampling and the number obtained was 12 companies. Data analysis method using multiple regression, classical assumptions, and SPSS assistance. The results of this research show that the company size variable has a negative effect on profitability. The leverage variable has a negative effect on profitability. The liquidity variable has a positive effect on profitability. The cash turnover variable has a negative effect on profitability. Keywords: firm size, leverage, liquidity, cash turnover, profitability